ANALISIS STRATEGI PEMASARAN UNTUK MENINGKATKAN DAYA SAING PADA USAHA PRODUK TAS LIMBAH MASKER (TALIMA) - Kokoh Tangga; Rahmat Dilta Harahap; Bunga Wirda; Desi Maulida; Safrida Safrida (universitas teuku umar, 2021)
The significant increase in business units has resulted in every business actor competing to attract the interest of potential consumers and maintain confidence in the goods offered. One of the efforts in realizing this is by implementing various marketing management strategies so that the target market is able to answer the objectives of the marketing. This research has the aim of getting an overview of the marketing strategy to increase competitiveness and to find out how effective the marketing strategy has been by the TALIMA Product business. This study uses a descriptive research method with a qualitative approach. The location of the research was carried out at the TALIMA Sales Outlet at BUMG Gampoeng Pasie Pinang, Mereubo District, West Aceh Regency in July- August 2021. Data collection techniques were through documentation, interviews and observations. The data analysis technique used content analysis (documentation research) and descriptive analysis. The results of the analysis of the effectiveness of marketing strategies show that there is an increase in sales from the previous month and can be used as a reference in developing more complex marketing strategies.Keywords: Marketing Strategy, Competitiveness, TALIMA